Iluminação a LED – avaliação das lâmpadas LED disponíveis para o consumidor brasileiro - Miguel de Souza, Teófilo; Rodriguez dos Santos, Humberto (Latin American Journal of Energy Research, 2024)
Lighting consumes around 15% of available electrical energy. Our day-to-day way of life demands that the environment around us adapts to what we need. Light bulbs, a century-old invention, in continuous evolution, have come in different forms and technologies. The moment is LED lighting, which is leading to the discontinuity of several other technologies. In this work, we chose some widely used brands to evaluate their performance, and to do so we used the Ponto de Luz laboratory, on the premises of UNESP, to shed a little light on the subject.